Guidelines for Sustainable Tribe Cultural Tourism Development / แนวทางการพัฒนาการท่องเที่ยวเชิงวัฒนธรรมชนเผ่าเพื่อความยั่งยืน - รัฐนันท์ พงศ์วิริทธิ์ธร, Ratthanan Pongwiritthon; ภาคภูมิ ภัควิภาส, Pakphum Pakvipas1 (Journal of Community Development Research (Humanities and Social Sciences); Vol 6 No 1 (2556): January - June 2013, 2014)
การพัฒนาปรับปรุงแหล่งท่องเที่ยวทั้งที่เป็นธรรมชาติ วัฒนธรรม และเชิงสร้างสรรค์ ให้เหมาะสมกับศักยภาพ การรองรับ (Carrying Capacity) ภายใต้โครงการที่สาคัญของรัฐ ให้จังหวัดเชียงใหม่เป็นศูนย์กลางการบิน (Hub) ของภูมิภาค เพื่อรองรับนักท่องเที่ยวทั้งชาวไทยและต่างประเทศที่มีเวลาเหมาะสมกับแผนการท่องเที่ยว โดยส่งเสริมและ การพัฒนาอุทยานดอยปุยในด้านอาชีพ มีจัดการธุรกิจในชุมชนอย่างมีความตระหนักคิด เป็นมิตรกับสิ่งแวดล้อม จึงมีความจาเป็นที่ต้องให้ศึกษาโดยหน่วยงานและกลุ่มผู้ทรงคุณวุฒิในด้านข้อมูลพื้นฐานและข้อมูลในมิติของศักยภาพการรองรับทางการท่องเที่ยว การวิจัยนี้มีจุดประสงค์เพื่อศึกษา วิเคราะห์และหาข้อเสนอแนะเกี่ยวกับข้อมูลโครงสร้างพื้นฐานในปัจจุบัน ทางสังคม เศรษฐกิจ วิถีชีวิตประจาวัน วิถีความเป็นชุมชน และข้อมูลในมิติของศักยภาพการรองรับทางการท่องเที่ยว เชิงวัฒนธรรมชนเผ่าเพื่อความยั่งยืน ซึ่งการเก็บข้อมูลเชิงคุณภาพ ใช้วิธีเลือกกลุ่มตัวอย่างแบบไม่ใช้ความน่าจะเป็น การเลือกตัวอย่างแบบเจาะจงจากประชากร ได้แก่ ผู้บริหารและเจ้าหน้าที่เทศบาลตาบลสุเทพ อาเภอเมือง จังหวัดเชียงใหม่ ชาวชุมชนหมู่บ้านม้งขุนช่างเคี่ยน อาเภอเมือง จังหวัดเชียงใหม่ ที่เป็นผู้ประกอบการร้านค้า จานวน 150 ราย โดยเก็บรวบรวมข้อมูลจากการสัมภาษณ์แบบมีโครงสร้างและรวบรวมข้อมูลจากแบบบันทึกรายละเอียดสถิติและข้อมูล ผลการวิจัย พบว่า ชุมชนดอยปุยมีศักยภาพการรองรับการพัฒนาการท่องเที่ยวเชิงวัฒนธรรมชนเผ่าในทุกด้าน ได้แก่ ความดึงดูดใจ ความสามารถเข้าถึงได้ทั้งทางกายภาพ แนวคิดและประเพณีวัฒนธรรม การมีที่พักอาศัยหรือที่พักผ่อนหย่อนใจที่ดีพอสมควร การมีกิจกรรมที่เป็นทั้งเชิงวัฒนธรรมและเป็นไปตามธรรมชาติของท้องถิ่น และความประทับใจ ทั้งทางด้านสถานที่พักและความประทับใจทางธรรมชาติ แนวทางการพัฒนาการท่องเที่ยวเชิงวัฒนธรรมชนเผ่าอย่างยั่งยืน ควรมุ่งเน้น 1) บริหารการจัดระบบแหล่งท่องเที่ยวเชิงนิเวศและการท่องเที่ยวเชิงวัฒนธรรมชุมชนให้เกิดประสิทธิภาพในมิติต่างๆ ให้สอดรับกับวิถีชีวิต วัฒนธรรมและระบบนิเวศของชุมชน 2) ต้องให้ความรู้ แลกเปลี่ยนความรู้ในด้านต่างๆ เพื่อผลในมิติของการพัฒนาการท่องเที่ยวที่ยั่งยืน 3) การกาหนดกฎกติกาและจัดการร่วมกันในด้านการจัดการสิ่งปฏิกูลเพื่อดารงไว้ของวัฒนธรรมชนเผ่า 4) การตลาด ควรเพิ่มการประชาสัมพันธ์ผ่านสื่อต่างๆ และสร้างผลิตภัณฑ์ต้องมีอัตลักษณ์ ความโดดเด่น และสื่อถึงการ สืบสานวัฒนธรรมชนเผ่า คำสำคัญ: การท่องเที่ยวเชิงวัฒนธรรม ชนเผ่า ความยั่งยืน The development and improvement of tourist attraction for natural, cultural and creative tourism to fit as the carrying capacity under the government project to promote Chiang Mai, as an aviation hub of the region to be able to accommodate both Thai and foreign tourists, who have a proper time for the travel plans, which is an important area for tourism development. With the promotion and development of career from Doi Pui National Park, there is a management of community business on environmental friendly awareness. Therefore it is necessary to be done by cooperating between organizations and external committees in perspective of basic information and capacity dimension information for accommodating tourism. The objectives of this study are as follows: first, to analyze and give recommendations about present basic infrastructure in perspectives of social, economic, life style, and community folk life. Second, is to explore carrying capacity dimensions of community in order to sustain their “Tribal Cultural Tourism”. Both qualitative analysis and quantitative analysis were applied in this study with the purposive non-probablility sampling. The sample was drawn from 150 stakeholders as follows first, local administrators and staff of Tambon Suthep Municipality. Second, community (Mong Village) who were owners of businesses at Baan khun Chang Kain, Aumphur Muang, Chiang Mai. Finally, local administrators and staff at Doi Suthep-Pui National Park. Questionnaires were conducted as a tool to collect data by the in depth-interview (structured interviews). The results indicated that Doi Pui community had all carrying capacity dimensions for developing Tribal Cultural Tourism which were as follows: attraction, accessibility, appropriateness of accommodation or rest areas and amenity especially from accommodations and nature. The tendencies of sustainable developing “Tribal Cultural Tourism” are as follows: first, develop eco-tourism management system. Second, exchanging and acknowledging information related to tourism management, which would result in sustainable tourism management. Third, set up policies for managing waste and disposals in community in order to preserve the traditional culture. Finally, in the marketing perspective they should emphasize integrated marketing communication, especially on advertising through the media and in terms of or product community, they should maintain their traditional culture in order to be unique. Keywords: Cultural Tourism, Tribe, Sustainability
Keywords: การท่องเที่ยวเชิงวัฒนธรรม ชนเผ่า ความยั่งยืน Cultural Tourism, Tribe, Sustainability